Translational Diffusion Measurements by Micro-coil NMR in Aqueous Solutions of the Fos-10 Detergent-Solubilized Membrane Protein OmpX - Horst, Reto (2012)
Aqueous solutions of the detergent Fos-10 (n-decylphosphocholine) without and with addition of the integral membrane protein (IMP) OmpX (outer membrane protein X) have been characterized using pulsed field gradient-stimulated echo (PFG-STE) NMR experiments for measurements of translational diffusion coefficients. Effective diffusion coefficients for Fos-10 micelles in the absence of OmpX were obtained by observation of NMR signals from 10-bromodecan-1-ol that had been inserted into the micelles, and in the presence of OmpX by NMR observation of the protein. It is thus shown that solutions of Fos-10-reconstituted OmpX can be quantitatively described as a mixture of Fos-10 monomers, uniform Fos-10 micelles and uniform OmpX-containing Fos-10 micelles, with Fos-10 monomers in fast exchange between the pools of these three species. This result establishes an avenue for efficient determination of the effective translational diffusion coefficients of IMP-containing detergent micelles based on observation of the intense detergent NMR signals, which is also applicable with unlabeled IMPs. This monitoring of the species present in a given IMP solution contributes to improved guidelines for rational selection of detergent and buffer conditions in structural studies of integral membrane proteins.